Implementation of Reading-Log to Increase Students’ Interest on Literacy at Islamic Boarding School - Kalsum Kalsum; Faridah Abdul Rauf; Ahmed Sardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aims to investigate the implementation of reading log to students’ reading. This study focuses on reading log and students’ interest in literacy. Reading log, it is hoped that students will be able to become a tool to control reading as well as a tool to measure students' interest in literacy. To obtain the research objectives, the researcher implemented quantitative research with one shot case study deign. The research was conducted Pondok Pesantren Zubdatul Asrar Parepare. The instruments in this study are reading log and questionnaires about students’ interest in literacy. Based on the analysis, by implementing the reading log, the results are as follow: 1) students can know exactly what they read, 2) reading became enjoyment and meaningful, 3) students are able to think critically, 4) the students are in time to complete their task in reading log.